2021
DOI: 10.3390/pathogens10121630
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Genotype and Antimicrobial Resistance between Campylobacter spp. Isolated from Organic and Conventionally Produced Chickens in Sweden

Abstract: Antibiotic resistance is a major challenge worldwide and increased resistance to quinolones in Campylobacter is being reported. Analysis of antibiotic resistance was performed on 157 Campylobacter strains (123 C. jejuni and 34 C. coli) from conventional and organic chickens produced in Sweden. Susceptibility for tetracycline, ciprofloxacin, erythromycin, nalidixic acid, streptomycin, and gentamycin was determined by microdilution. All 77 isolates from organic chickens were sensitive to all antibiotics, except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In Sweden, Hansson et al [ 43 ] found that Campylobacter jejuni isolated from conventionally raised chickens showed a higher occurrence of resistance to the quinolones nalidixic acid and ciprofloxacin compared with C. jejuni isolated from organic chickens. This difference between isolates from different production systems agrees with findings in other studies on organic and conventional poultry as well as poultry meat [ 43 ].…”
Section: Methodology Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, Hansson et al [ 43 ] found that Campylobacter jejuni isolated from conventionally raised chickens showed a higher occurrence of resistance to the quinolones nalidixic acid and ciprofloxacin compared with C. jejuni isolated from organic chickens. This difference between isolates from different production systems agrees with findings in other studies on organic and conventional poultry as well as poultry meat [ 43 ].…”
Section: Methodology Of the Literature Reviewmentioning
confidence: 99%
“…In Sweden, Hansson et al [ 43 ] found that Campylobacter jejuni isolated from conventionally raised chickens showed a higher occurrence of resistance to the quinolones nalidixic acid and ciprofloxacin compared with C. jejuni isolated from organic chickens. This difference between isolates from different production systems agrees with findings in other studies on organic and conventional poultry as well as poultry meat [ 43 ]. Williams et al [ 44 ] did not find any detectable difference in Campylobacter carriage in fast- and slow-growing birds, but artificial infection with C. jejuni affected the incidence of hock marks and pododermatitis, which was greater in the fast-growing breed than in their slower-growing counterparts.…”
Section: Methodology Of the Literature Reviewmentioning
confidence: 99%
“…However, a study reported a significantly lower fluoroquinolone resistant Campylobacter prevalence (< 2%) in organic than in conventional (46%) poultry farms [136]. Susceptibility test of 157 Campylobacter isolates from organic (n = 77) and conventional (n = 80) chickens showed that all organic isolates were sensitive to all antibiotics, except two that were resistant to tetracycline, while resistance to quinolones and tetracycline were observed among the 80 isolates from conventional chickens [172]. Despite limitations, fecal, carcasses, equipment, water and air sample analyses from organic and conventional processing methods suggested that raising birds without the use of antimicrobials is not effective in decreasing the incidence of AMR Campylobacter in poultry products [146].…”
Section: Campylobacter Sppmentioning
confidence: 96%
“…Mechanistic insight into how, when, and where organic farming practices substantially and reliably reduce the prevalence and spread of antimicrobial resistance could be used to formulate scalable solutions for conventional farming practices with benefits for both agriculture and public health. However, our understanding of the extent to which organic farming practices can successfully reduce the emergence and spread of AMR remains fragmentary — and hotly debated 12 15 . Empirical evidence linking specific farming practices to patterns of antimicrobial resistance remains difficult to establish, in part because the relationship between antimicrobial use and drug resistance varies dramatically across contexts, depending on environmental conditions, livestock hosts, and pathogens.…”
Section: Introductionmentioning
confidence: 99%